Inhibition of Clotting as the Result of Plasminogen Activation by Streptokinase - Glas, P; Beller, F. K (Thrombosis and Haemostasis, 1960)
Samples of an activation mixture, consisting of fibrinogen, streptokinase and plasma (source of pro-activator) were added to thrombin at intervals of 1 minute and subjected to lysis time determinations; the absence of clotting was noted after a certain period of incubation. At this point, the lysis time was no longer measurable.Inhibition of coagulation was not observed if either bovine fibrinogen or human plasma were incubated with streptokinase alone. If, however, human fibrinogen was used instead of bovine fibrinogen, this effect occurred even if only fibrinogen and streptokinase were incubated.The mechanism of the process described was investigated by varying the different streptokinase- and fibrinogen concentrations, using either undiluted or diluted plasma.It was evident that there is a relationship between the concentrations of fibrinogen and streptokinase on the one hand, and the degree of plasma dilution on the other.Fibrinogenolysis is caused by activation of the pro-enzyme contained in the fibrinogen preparations. During this process, fibrinogen is altered to a non-coagulable protein.